KEJADIAN SKABIES DI LINGKUNGAN PONDOK SOSIAL KEPUTIH SURABAYA TAHUN 2016 - Ratri Dewi Puspa Ningrum; Rusmiati .; Winarko . (GEMA LINGKUNGAN KESEHATAN, 2016)
Scabies is a skin disease caused by Sarcoptes scabei mite. 112 female occupants of Liponsos Keputih suffer from scabies. This study aims to determine the relationship between personal hygiene behavior with scabies incident in  Liponsos of  Keputih,  Surabaya 2016. This research was conducted by analytical method and categorized as research. The population in this study were residents of female occupant. 82 occupants were chosen as  sample by systematic sampling technique. Data collection using questionnaire- sheet, observation sheets, and measurement. This study shows that there was a relationship between personal hygiene behavior and scabies incidence in  Liponsos of  Keputih,  Surabaya. It is advised for the management of Liponsos Keputih to improve sanitation and conduct counseling or distribute of leaflets on scabies. Keywords : Scabies Cases, Personal Hygiene Behavior, environmental Sanitation.